Netherlands : 2013 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
The Netherlands is an AAA euro area (EA) economy with significant private sector imbalances. The main policy challenge is to restore growth and manage downside risks while allowing for an orderly adjustment of private sector balance sheets. A focus on medium-term objectives will cement policy credibility and mitigate uncertainty. The financial system must reduce its dependence on wholesale financing, and banks reliant on public sector support need to wind down this support. Reforms in the labor markets and human capital will be important in safeguarding the economy's growth potential.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet